Social protection floor gaps and pandemic relief measures: A case for universalism? Exploring scalability through targeted versus universalist approaches - Annalena Oppel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
With the expansion of social protection measures due to the COVID-19 pandemic, considerations both old and new have surfaced regarding targeted versus universalist approaches. This study focuses on how social protection coverage before the pandemic influences the extent of targeted versus universalist policies in advanced and developing economies. It offers new insights regarding continued and new patterns in policy design, particularly concerning beneficiaries and the type of programmes, by learning from the policy mix of crisis relief. The study draws on two datasets: the COVID-19 Stimulus Tracker and the Social Protection Floor Index. Combined, they provide information about financing gaps for social protection floors before the pandemic and about countries' specific pandemic policy responses. Using standard regression modelling, an association is estimated between social protection floor indexes and the share of universal policy measures across different conceptualizations of social protection. The findings offer first reflections on the extent to which pre-existing systems matter and in what way recent policy innovations may inform the design of shock-responsive systems going forward.
Keywords: D60; H12; H53; I30; 330; crisis response; social protection floors; universal social protection; targeting; universalism; economic shocks